Health economics and healthcare reform breakthroughs in research and practice (Medical Information Science Reference, 2018)
"This book is a comprehensive source of academic material on the importance of economic structures and policy reform initiatives in modern healthcare systems. Highlighting a range of pertinent topics such as clinical costing, patient engagement, and e-health"--Provided by publisher.